Knowledge Structure and Training of Translation Teachers: An Exploratory Study of Doctoral Programmes of Translation Studies in Hong Kong - Li, Defeng; Zhang, Chunling (Meta, 2011)
A rapid expansion of translation programmes at all levels the world over in recent years has heightened the demand for quality translation teachers. However, little research has been carried out to date on translation teacher training – M.Phil./Ph.D. programmes of translation studies in tertiary institutions despite a plethora of studies on general translation teaching. The present study, intended as an initial attempt to address the issue, approaches the topic from a teacher education perspective and looks critically at the knowledge structure of translation teachers. On this basis, the present article reports on a qualitative case study conducted in 2004-2007 on the curriculums and particularly the needs and experiences of the research students at the M.Phil./Ph.D. programmes of translation studies in Hong Kong. Although the study was conducted in the context of Hong Kong, the findings and implications may apply to other translation teacher training programmes the world over.